Age relative height, weight and body mass index percentiles of children in Jos, North-Central Nigeria - Mosugu, Ovayoza O.; Shinku, Francis; Nyam, Jacob C.; Mador, Emmanuel S. (Asian Journal of Medical Sciences, 2021)
Background: Interpretation of body mass index in children is quite different from that in adults which use standard weight status categories that are the same for all ages and for both men and women. Aims and Objective: The study was aimed at determining the prevalence of childhood obesity in Jos. Materials and Methods: A total of 371 children were enrolled in the study. Weight was taken with only light clothing and without foot wears. Height obtained without head-gears or shoes and the measuring flat tops pressed down to avoid errors due to tall hair. Body mass index were calculated for each subject as ratio of body weight to body height. All data were analyzed statistically and separately for different ages and the mean values for height against age, weight against age, height against weight and BMI for age was obtained with centiles of absolute deviations from the mean. Results: The age of the studied population ranged from 3 – 14 years with mean of 8.4 ± 2.8. Height of the children on the other hand ranged from 0.9 – 1.64 meters with mean value of 1.26 ± 0.15 and their weight ranged from 10 – 76 kg with mean value of 25.6 ± 9.2. Out of the 371 children studied, 14 (3.8%) were found to be underweight, 302 (81.4%) had healthy weight while 41 (11%) were at risk of overweight and 14 (3.8%) were overweight. In addition, the body mass index of girls was found to be significantly higher than those of boys at 12 and 13 years only. Conclusion: It is concluded that the prevalence of childhood obesity is high in Jos, North-central Nigeria.